Pengaruh Iklim Organisasi, Self Efficacy, dan Motivasi Berprestasi Terhadap Kinerja Guru SMK Tamtama Kroya - Azizah, Mariyatun Yami; Azizah, Siti Nur (Jurnal Ilmiah Mahasiswa Manajemen, Bisnis dan Akuntansi (JIMMBA), 2023)
This study aims to examine the influence of organizational climate, self-efficacy, and achievement motivation on the performance of SMK Tamtama Kroya teachers. The sampling technique used is the census method (saturated sample) so that the entire population is used as a sample. Respondents in this study were all 49 Tamtama Kroya SMK teachers. This research uses descriptive and statistical analysis methods including, validity, reliability, classical assumption testing, multiple regression analysis, and hypothesis testing using t-test and F test. The t or partial test shows that organizational climate variables, self-efficacy, and achievement motivation have partially significant effects on the performance of SMK Tamtama Kroya teachers. The simultaneous test shows that the variables of organizational climate, self-efficacy, and achievement motivation simultaneously influence the performance of Tamtama Kroya SMK teachers. The coefficient of determination also shows that organizational climate, self-efficacy, and achievement motivation affect the performance of SMK Tamtama Kroya teachers by 0.598 or 59.8% variation in performance can be explained by variations in the three independent variables, namely organizational climate, self-efficacy, and motivation achievement, while the remaining 40.2% is influenced by other variables.